Supporting the development of a professional identity: General principles - Cruess, Sylvia R.; Cruess, Richard L.; Steinert, Yvonne (Medical teacher, 2019)
While teaching medical professionalism has been an important aspect of medical education over the past two decades, the recent emergence of professional identity formation as an important concept has led to a reexamination of how best to ensure that medical graduates come to "think, act, and feel like a physician." If the recommendation that professional identity formation as an educational objective becomes a reality, curricular change to support this objective is required and the principles that guided programs designed to teach professionalism must be reexamined. It is proposed that the social learning theory communities of practice serve as the theoretical basis of the curricular revision as the theory is strongly linked to identity formation. Curricular changes that support professional identity formation include: the necessity to establish identity formation as an educational objective, include a cognitive base on the subject in the formal curriculum, to engage students in the development of their own identities, provide a welcoming community that facilitates their entry, and offer faculty development to ensure that all understand the educational objective and the means chosen to achieve it. Finally, there is a need to assist students as they chart progress towards becoming a professional.